Making Scenes Reggae, Punk, and Death Metal in 1990s Bali - Baulch, Emma (e-Duke books scholarly collection, 2007)
In 1996, Emma Baulch went to live in Bali to do research on youth culture. Her chats with young people led her to an enormously popular regular outdoor show dominated by local reggae, punk, and death metal bands. In this rich ethnography, she takes readers inside each scene: hanging out in the death metal scene among unemployed university graduates clad in black T-shirts and ragged jeans; in the punk scene among young men sporting mohawks, leather jackets, and hefty jackboots; and among the remnants of the local reggae scene in Kuta Beach, the island's most renowned tourist area. Baulch tracks how each music scene arrived and grew in Bali, looking at such influences as the global extreme metal underground, MTV Asia, and the internationalization of Indonesia's music industry.Making Scenes is an exploration of the subtle politics of identity that took place within and among these scenes throughout the course of the 1990s. Participants in the different scenes often explained their interest in death metal, punk, or reggae in relation to broader ideas about what it meant to be Balinese, which reflected views about Bali's tourism industry and the cultural dominance of Jakarta, Indonesia's capital and largest city. Through dance, dress, claims to public spaces, and onstage performances, participants and enthusiasts reworked "Balinese-ness" by synthesizing global media, ideas of national belonging, and local identity politics. Making Scenes chronicles the creation of subcultures at a historical moment when media globalization and the gradual demise of the authoritarian Suharto regime coincided with revitalized, essentialist formulations of the Balinese self